PREVALENCE AND PREDICTORS OF RESPIRATORY SYMPTOMS AMONG KAZAKHSTANI COAL MINERS - Kassymova, Aida (Nazarbayev University School of Medicine, 2024)
Underground coal mining has been a crucial part of Kazakhstan’s economy for the last 30 years, yet little is known about the burden of respiratory disease and trauma among Kazakhstan miners. A cross-sectional survey among a random sample of working miners was conducted; demographic, work, and health information were collected using a standardized questionnaire.
Keywords: Type of access: Embargo; Kazakhstan; coal miners; respiratory symptoms; occupational health predictors